Life satisfaction evaluation in earthquake-hit area by the probabilistic linguistic GLDS method integrated with the logarithm-multiplicative analytic hierarchy process. (August 2019) - Liao, Huchang; Yu, Jinyan; Wu, Xingli; Al-Barakati, Abdullah; Altalhi, Abdulrahman; Herrera, Francisco
Abstract: Occurred on May 12, 2008, the Wenchuan earthquake in China has received worldwide attention for its incredible destructive power. In June of the same year, the State Council issued a draft regulation on post-quake restoration and reconstruction. To find the effect of post-earthquake reconstruction, this paper measures the residents' life satisfaction in Wenchuan by multiple criteria decision-making methods under probabilistic linguistic environment. Based on field surveys and domains of life satisfaction, an indicator system is proposed as a framework to collect resident's evaluations. To retain as much original information as possible, an effective weighting method with probabilistic linguistic information is developed to deduce the indicator's importance. It extends the logarithm-multiplicative analytic hierarchy process to handle the probabilistic linguistic evaluations and derive the criteria weights in interval forms. In this way, the inherent uncertainty of the evaluations on the importance of life satisfaction indicators can be reflected. Furthermore, a novel outranking method named the probabilistic linguistic gain and lost dominance score method, is used to obtain the overall life satisfaction degrees of the residents in Wenchuan. We apply this method to measure the life satisfaction degrees of residents in two areas. The calculation results show that the life satisfaction degrees of the residents in the earthquake-hit area are higher than those of the residents in the non-earthquake area.